Pengaruh Asesmen Otentik Dengan Asesmen Tradisional Dalam Meningkatkan Keterampilan Berpikir Kritis Siswa (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This study aims to analyze meaningful and effective learning assessments applied in the classroom. This research method uses Literature Review by reviewing 12 articles that are in accordance with the material discussed. The results showed that authentic assessments, which involve contextual and relevant tasks, were more effective in improving critical thinking skills than traditional assessments that focused on repetition of information. These findings are supported by Bloom's theory of constructivism and taxonomy, as well as previous studies that show that authentic assessment also increases learning motivation. Students are able to demonstrate what they understand about the learning carried out in accordance with the context of their lives. This will be effective if it is more formative that provides various information in the form of continuous feedback for teachers and students. The implication of this study is the importance of implementing authentic assessments in the curriculum and teaching strategies to maximize the development of students' critical thinking skills, in order to face the challenges of the 21st century.